Effect of handrubbing using locally-manufactured alcohol-based handrubs in paediatric wards in Harare, Zimbabwe. Issue 1 (December 2017) - Gudza-Mugabe, Muchaneta; Magwenzi, Marcelyn; Mujuru, Hilda; Bwakura-Dangarembizi, Mutsa; Robertson, Valerie; Aiken, Alexander
Abstract We assessed bacterial contamination of hands of adults present in paediatric wards in two tertiary-care hospitals in Harare, Zimbabwe and the microbiologic efficacy of locally-manufactured alcohol-based hand rub (ABHR). During unannounced visits, samples were collected using hand-print and hand-rinse methods. Samples were collected from 152 individuals (16 nurses, 10 doctors, 28 students, 86 parents/guardians, 12 others). Contamination of hands with Gram-negative bacteria was found in 91% of adults tested with a mean of 14.6 CFU (hand-rinse method; IQR 3–65), representing a high risk for transmission of pathogens potentially leading to nosocomial infections. A single application of ABHR under controlled conditions achieved an average of 82% (or 0.72 log) reduction in detectable counts. Amongst 49Enterobacteriaceae isolates from hands, 53% were resistant to gentamicin and 63% were resistant to cefpodoxime. Use of ABHR represents an attractive intervention for reducing nosocomial infections in this setting.